The quality of vernacular functional spaces based on Salinger residence - GhaffarianHoseini, AmirHosein; Ibrahim, Rahinah; Baharuddin, Mohd Nasir (2009)
The quality of contemporary residential functional spaces has been mostly based on style and modernization rather than the tradition of particular regional context. With the rapid modernization of Malaysia, the kampong house as a Malay vernacular architecture has been replaced by modern architecture. Several aspects of kampong which identified it as a major vernacular value, has been lost inside contemporary functional spaces. In this research, a case study research method will be conducted to study the vernacular architectural features of Malay vernacular houses. These features include spatial characteristics of functions and spaces based on local needs which influence the quality of functional spaces. The Salinger house, a unique symbol of Malaysian vernacular architecture, has been selected as a single case study for this research. Consequently, this research found that the vernacular functional spatial features could be integrated successfully into contemporary functional spaces